WIPO and the Sustainable Development Goals. - World Intellectual Property Organization (Geneva, Switzerland : World Intellectual Property Organization, 2019)
"Intellectual property as a policy exists to create an enabling environment for- and to stimulate investment in- innovation; to create a framework in which new technologies can be traded around the world and shared. The economic imperative at the heart of innovation is fundamental to the process of societal transformation that the Sustainable Development Goals aim to achieve."--Page 3
Pages 6 & 7 folded to form timeline: "200 years of transformative innovation driving human progress".
Keywords: Sustainable Development Goals; Intellectual property (International law); Sustainable development -- Law and legislation